2021
DOI: 10.1111/jce.15010
|View full text |Cite
|
Sign up to set email alerts
|

Navigating inferior vena cava filters in invasive cardiology procedures: A systematic review

Abstract: Background: Transfemoral venous access (TFV) is the cornerstone of minimally invasive cardiac procedures. Although the presence of inferior vena cava filters (IVCFs) was considered a relative contraindication to TFV procedures, small experiences have suggested safety. We conducted a systematic review of the available literature on cardiac procedural success of TFV with IVCF in-situ.Methods: Two independent reviewers searched PubMed, EMBASE, SCOPUS, and Google Scholar from inception to October 2020 for studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…30 More recently, a large single centre series has reported on the feasibility of complex transfemoral EP procedures in the majority of patients with IVC filters. 31 A systematic review by Shah et al, 32 has also demonstrated safety and feasibility of transfemoral access, and hence a standard inferior approach may still be first-line in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…30 More recently, a large single centre series has reported on the feasibility of complex transfemoral EP procedures in the majority of patients with IVC filters. 31 A systematic review by Shah et al, 32 has also demonstrated safety and feasibility of transfemoral access, and hence a standard inferior approach may still be first-line in such patients.…”
Section: Discussionmentioning
confidence: 99%